12. ANALISIS KINERJA KEUANGAN SEKTOR PUBLIK - Saryadi, Saryadi (FORUM, 2008)
Local govenment has an obligation to present its local financial responsibility report to be judged, whethe or not local government successfully conducting their job or not. One of the tool use to analyze government’s performance is managing its local financial performance is financial ratio on APBN that has been set up and proceed. Some ratios developed based on APBD financial datas are : autonomy piscal, efectivity pohor.